Evening and night work schedules and children's social and emotional well-being - Till Kaiser; Jianghong Li; Matthias Pollmann-Schult (Community, Work & Family, 2019)
An emerging body of evidence shows that parents' non-standard work schedules have a detrimental effect on children's well-being. However, only a limited number of studies have investigated mediating factors that underpin this association. Likewise, only a few studies have examined the impact of fathers' non-standard work schedules on children's well-being. Based on data from the Families in Germany Study (FiD), this study aimed to address these research gaps. The sample consists of parents and their children at ages 7–8 and 9–10 (n0.167em=0.167em838 child observations in dual-earner families). The data were collected in the years 2010–2013. Non-standard work hours were defined as working in evenings and or at night (every day, several times a week, or changing as shifts). Children's social and emotional well-being was measured with the Strengths and Difficulties Questionnaire (SDQ). The findings show that both mothers' and fathers' evening and night work schedules are linked to an increase in children's externalizing and internalizing behavior and that this association is partially mediated by mothers' and fathers' harsh and strict parenting, with a stronger mediation effect for fathers parenting. – – Un conjunto de nueva evidencia sugiere que los horarios laborales no-estándar de los padres tienen un efecto perjudicial en el bienestar de los ni\~nos. No obstante, solamente un número limitado de estudios han investigado los factores intervinientes que sustentan esta asociación. Asimismo, son escasos los estudios que examinan el impacto de los horarios laborales no-estándar de los padres en el bienestar de los ni\~nos. Basada en datos del estudio `Familias en Alemania' (FiD, por sus siglas en alemán), esta investigación tiene el objetivo de abordar estas brechas de investigación. La muestra consiste en padres y sus hijos entre 7–8 y 9–10 a\~nos de edad (n0.167em=0.167em838 observaciones de ni\~nos en familias con doble fuente de ingresos). Los datos fueron recopilados durante los a\~nos 2010–2013. Las horas de trabajo no-estándar se definen como horas trabajadas por las tardes o por la noche (diariamente, varias veces a la semana o alternando en turnos). El bienestar social y emocional de los ni\~nos se midió con el Cuestionario de Fortalezas y Dificultades (SDQ, por sus siglas en inglés). Los resultados muestran que los horarios de trabajo vespertino y nocturno tanto de las madres como de los padres, están vinculados a un aumento en el comportamiento externalizado e internalizado de los ni\~nos, y que esta asociación está parcialmente mediada por la crianza severa y estricta por parte de las madres y los padres, teniendo la crianza paterna un efecto de mediación más fuerte.
Keywords: 330; non-standard work; children; social and emotional well-being; SDQ; dual-earner couples; parenting